Meta-Analysis of Collaborative Learning Approaches in Educational Management and Their Impact on Student Performance - M Karim; Syafrul Antoni; Karlini Oktarina (AKADEMI TEKNIK ADI KARYA, 2024)
This meta-analysis investigates the effects of collaborative learning approaches within the framework of educational management and their impact on student performance. Collaborative learning, as a student-centered instructional method, has been widely adopted across various educational levels and settings. However, its effectiveness in enhancing academic achievement remains a topic of debate. This study synthesizes findings from 12 empirical studies conducted between 2022-2024, covering primary, secondary, and higher education contexts globally. Using a random-effects model, the meta-analysis quantifies the overall effect size of collaborative learning approaches on student performance, while accounting for variations in geographical region, subject matter, and educational level. The results reveal a high to strong positive effect of collaborative learning on student academic performance (mean effect size = 0.819). Additionally, subgroup analyses show that the impact is more pronounced in subjects requiring higher-order thinking skills, such as science and mathematics, and in educational settings where collaborative learning is systematically supported by institutional management. The analysis also highlights key factors that influence the success of collaborative learning, including group dynamics, teacher facilitation, and the integration of technology.